Meningkatkan Kepedulian dan Peran Aktif Masyarakat dalam Memakmurkan Mushola Al-Taqwa SD Kanyoran di Kec. Semen Kediri Jawa Timur - Titin Widya Risni (Universitas Nurul Jadid, 2024)
This activity is prompted by the declining concern of the community towards Mushola At-Taqwa in Kediri, attributed to social and cultural changes, lack of spiritual understanding, and inadequate physical conditions. The aim of this community service is to enhance awareness towards the mosque through religious education, facility improvements, and the organization of engaging social and religious activities. The Participatory Action Research (PAR) method is utilized, involving active participation from students and the community. The results of this activity indicate that Mushola At-Taqwa has the potential to become a beneficial center for religious activities. Efforts to increase community awareness of various activities at the mosque are carried out through religious education, facility improvements, and other religious social activities. Activities include prayer education, mosque repairs, Friday Blessings programs, and Storytelling Safaris. The activities of Mushola At-Taqwa support SDG 4 Quality Education by enhancing the literacy, numeracy, morality, and character of students. Social and religious activities foster solidarity, tolerance, and patriotism. This contribution helps prepare resilient and moral young generations for a sustainable and prosperous future